Sports sponsorship: spectator's involvement and the effects on the identification and loyalty - Alejandro Alvarado Herrera; José Martí Parreño; Ma. Walesska Schlesinger (Management Letters/Cuadernos de Gestión, 2012)
Sports sponsorship has increased notably during the last years being used by brands not only as a key tool of their marketing communications but even their market positioning. This research analyzes the influence of sports spectator's involvement to motorcycling -specifically MotoGP- in identification and loyalty to their favourite pilot. The ability of managers to generate profits from stakeholders such as sponsors and the media is directly related to size and loyal viewers identified an athlete or team, hence the importance in this area of these variables. A cross-sectional empirical research, based on the literature on consumer involvement and its relationship to loyalty and identification, providing a basis for contrast, by using technical analysis of covariance structures, the proposed theoretical model. Study results reveal that consumer involvement with a sport direct influence, both positively and significantly in their identification as their loyalty to their favourite pilot. Managerial implications of the findings and future research areas are also discussed.